Halide perovskite solar cells - Li, Zhe (Nanyang Technological University, 2024)
This report investigates various methods for slot die coating perovskite films using green solvents γ-valerolactone (GVL), and γ-butyrolactone (GBL), under ambient conditions. The study uses an off-stochiometric two-step deposition method under slot die coating. The study focuses on optimizing coating parameters, including coating speed, wet film thickness, and base temperature, to achieve the best perovskite film quality. Additional techniques, such as antisolvent bathing were introduced to further enhance film formation and uniformity. The results demonstrate that the use of green solvents, both individually and in mixtures, can produce promising perovskite films while minimizing environmental impact. These findings have potential applications for sustainable and scalable industrial production of perovskite solar cells, contributing to the overall sustainability of the industry.